Etiology and Clinical Profile of Chronic Cough in Children (Dhaka Shishu (Children) Hospital Journal, 2021)
Background: Cough in children is one of the most common presenting symptoms to pediatricians. Acute cough lasts less than 3 weeks, subacute 3-8 weeks and chronic cough more than 8 weeks.Objectives: To find out the etiology and clinical profile of chronic cough in pediatric age group.Methods: This descriptive type of cross-sectional study was carried out in the Department of Respiratory Medicine at Dhaka Shishu Hospital, Dhaka, Bangladesh from September 2017 to August 2018 for a period of one year. Purposive sampling technique was used to select the patients. Patients with the age 6 month to 12 years who were suffering from chronic cough for more than 8 weeks were included as study population.Results: Family history of asthma was found in 36(72.0%) cases. Common clinical factors like allergic rhinitis, eczema, allergic conjunctivitis, trigger agent were found in 28(56.0%), 9(18.0%), 2(4.0%) and 50(100.0%) cases respectively.Conclusion: Family history of asthma was found in majority cases of chronic cough. Allergic rhinitis, eczema, allergic conjunctivitis and trigger agent were common clinical factors associated with chronic cough patients.DS (Child) H J 2019; 35(1) : 33-36